Average demands and most demanding passages of national-level female soccer matches: do small- and large-sided games replicate match demands? - Savolainen, E. H. J.; Vänttinen, T.; Peltonen, J.; Ihalainen, J. K.; Walker, S. (Frontiers in Sports and Active Living, 2023)
Introduction: This study aims to (1) determine the average and most demanding passage (MDP) load of national-level female soccer matches and (2) evaluate the relationship between average and MDP load during small-sided games (SSGs), large-sided games (LSGs), and matches.